Neural mechanisms of muscle cramp - Nakagawa, K.; Miyamoto, N.; Kanosue, K. (Sports Performance, 2015)
Although muscle cramps are a common problem for many athletes, the underlying mechanisms are still poorly understood. In this chapter, we review the proposed causes of muscle cramps. Dehydration and electrolyte disturbance are generally considered to be causes of muscle cramps, but this is unlikely. Alternatively, either neural activity in the spinal cord or in the peripheral could be the cause of cramps. Definitive evidence is scarce and controversy abounds.